A kultúrfogalom fordítása: „Saját” és „idegen” Borisz Akunyin regényeiben és magyar fordításaiban - Sahverdova Nava, Vanda (Studia Litteraria, 2024)
In this paper I investigate how cultural concepts are transferred into the target language text during the translation process, to what extent the translator is able to represent the net of associations the concept has in the original language, to what extent it is translatable at all, and to what extent it can be considered a lacuna or equivalence-free element. A concept of culture that is part of a particular system will never fully correspond to a particular part of another linguistic system. In translating such a concept, we obtain a meaning which is part of the conceptual-semantic system of the language, but which is embedded in an unusual way in literary translation. On the other hand, the context can play a complementary role for the conceptual meaning, so that the literary translation may also transfer new, foreign conceptual meanings from the original language into the target language, which can then become a source of comprehension of the linguistic world picture.